Design of Fixed Wideband Beamformer through Improved Maximum Energy Approach - Rui Du; Yangyu Fan; Jianshu Wang (Journal of Electrical and Computer Engineering)
A maximum energy approach is investigated in this paper to design fixed wideband beamformer. This approach has been improved by integrating response variation (RV) into the target function to maintain the frequency invariant property of wideband beamformer over the whole passband. Two methods for designing null to suppress interference signal also have been proposed to make the wideband beamformer robust in complicated environment. Comparisons among other methods are provided to illustrate the effectiveness and enhancement of performance of the new approaches.